Universities are becoming major players in the national system of innovation - Walwyn, David; Cloete, Laurens (South African Journal of Science, 2016)
Based on data from South Africa’s research and development (R&D) surveys, the country’s R&D expenditure has grown in real terms by 52% over the period 2001 to 2012. This growth has been driven by government funding, which rose from 34% of the total funding in 2003 to 45% by 2012. Much of the additional funding has been granted to universities, with government support of R&D in this sector rising 450% in nominal terms, or 250% in real terms, over the same period. This funding focus, indicative of a growing role for universities as R&D performers within the national system of innovation, follows a pattern set earlier in many developed countries and reflects a revision in the state’s steering of knowledge creation. The R&D Survey also revealed a decline in the average cost of research, as expressed by expenditure per full-time equivalent researcher. This finding suggests that the researcher labour market is being better supplied and the constraints identified by earlier reviews are slowly being overcome. Both trends are highly positive for the research system. However, the 34% decline in business R&D expenditure since its peak in 2008 is a matter of concern and needs to be addressed. In particular, the level of state-industry embeddedness must be increased to encourage private investment and to overcome South Africa’s present growth constraints in respect of developing competitive medium- to high-technology sectors.